Miscarriage Induced Mental Health Issues and Coping Strategies among Primigravida Women - Parveen, Farzana; Channar, Husan Bano; Manzoor Syed, Binafsha; Brohi, Aftab; Ali Kori, Imtiaz; Sarwar, Sabeeha (Indus Journal of Bioscience Research, 2025)
Background: Miscarriage is most common with approximately 23 million miscarriages occurring worldwide annually. It induces mental health issues among primigravida women, which affects the overall well-being of a woman. Women experiencing miscarriage have higher levels of depression and general anxiety symptoms. Healthcare providers need to give proper information, and emotional and psychological support during the period of miscarriage. Aim of Study: To determine the mental health issues and identify the coping strategies used by primigravida women after miscarriage. Material and Methods: A quantitative descriptive cross-sectional study was conducted on 317 primigravida women at the Gynecological Ward and OPD of Liaquat University Hospital, Jamshoro. A non-probability purposive sampling method was utilized for data collection. Data was analyzed by using SPSS version 27. Frequency and percentages were computed for categorical variables. Numerical variables were summarized as mean ± standard deviation. The chi-square test was applied to assess the association of categorical variables with PTSD and coping strategies. Results: A total of 317 females were enrolled in the study. The mean age of study subjects was 28.1 ± 5.3 years. The average PCL-C score was 33.8 ± 8.6 with a score range of 17-60. Using a threshold of 38 and above, PTSD was seen in 38.8% of females. Out of 14 coping strategies, the highest mean score was seen for the strategy of acceptance and instrumental support followed by self-distraction, active coping, planning, denial, emotional support, religion, venting, positive reframing, behavioral disengagement, self-blame, humor and substance use. The highest PTSD frequency was seen in females of age group 20-29 years (40.8%). Conclusion: Miscarriage is a deeply emotional and psychologically challenging experience for women, especially primigravida women. The mental health of primigravida women after miscarriage is significant, influences women’s decisions to delay future pregnancy attempts, and underscores the need for significant emotional and social support.